KINERJA KEPALA MADRASAH TSANAWIYAH MU’ALLIMIN MUHAMMADIYAH ALABIO KECAMATAN SUNGAI PANDAN KABUPATEN HULU SUNGAI UTARA - N Nahrawi (Administraus, 2021)
Abstract: The purpose of this study was to determine the performance of the Head of Madrasah Tsanawiyah Mu'allimin Muhammadiyah Alabio, Sungai Pandan District, Hulu Sungai Utara Regency which was seen from the competence of the principal/madrasah in 5 dimensions, namely (1) supervision, (2) managerial, (3) entrepreneurship. , (4) personality, and (5) social. This research was conducted with a quantitative approach. The population in this study were the head of madrasah, teachers, and administrative staff totaling 26 people consisting of the principal, teachers, and administrative staff. The data collection instrument is a questionnaire/questionnaire with a Likert scale, which has 4 alternative answers, consisting of 22 items. The same research instrument was given to school principals, teachers and administrative staff. Analysis of one variable data from two types of respondents. The condition of an aspect of the variable is aligned, compared, with the aim of seeing the stability of the data. The reliability and condition of the data were checked with cross-responders. The next analysis is to compare the values of each item with the average value of all items as a limiter. The results of the study show that the 4 dimensions of supervision, managerial, personality, and social are good at 80% and the entrepreneurial dimension is bad at 20%. Keywords: Headmaster, Performance Abstrak: Tujuan penelitian ini adalah untuk mengetahui Kinerja Kepala Madrasah Tsanawiyah Mu’allimin Muhammadiyah Alabio Kecamatan Sungai Pandan Kabupaten Hulu Sungai Utara yang dilihat dari kompetensi Kepala sekolah/madrasah pada 5 dimensi yaitu (1) supervisi, (2) manajerial, (3) kewirausahaan, (4) kepribadian, dan (5) sosial. Penelitian ini dilakukan dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah Kepala Madarasah, Guru-guru, dan Staf tata usaha berjumlah 26 orang terdiri dari Kepala madrasah, Guru-guru, dan Staf tata usaha. Instrumen pengumpulan data berupa kuesioner/angket dengan skala likert, yang memiliki 4 alternatif jawaban, terdiri atas 22 butir. Instrumen penelitian yang sama diberikan kepada Kepala sekolah, Guru-guru dan Staf tata usaha. Analisis data satu variabel yang berasal dari dua jenis responden. Kondisi suatu aspek dari variabel disejajarkan, dibandingkan, dengan maksud melihat kemantapan data. Reliabilitas dan kondisi data dicek dengan responden silang. Analisis selanjutnya adalah membandingkan nilai-nilai setiap butir dengan rata-rata nilai semua butir sebagai pembatas. Hasil peneltian menunjukkan bahwa 4 dimensi supervisi, manajerial, kepribadian, dan sosial baik sebesar 80% dan dimensi kewirausahaan buruk sebesar 20%. Kata Kunci: Kinerja, Kepala Sekolah